2023
DOI: 10.3390/bs13040326
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Adolescent Life Goals in Contemporary China: A Mixed-Methods Study

Abstract: Adolescence is a developmental period when individuals actively evaluate and construct their life goals. During the past several decades, China has transformed dramatically toward a highly competitive, market-oriented society. Despite a growing interest in exploring the implications of cultural values for youth adjustment in contemporary China, little is known about what life goals are prevalent among Chinese adolescents. This mixed-methods study aimed to identify the key themes of life goals and to examine ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Considering that adolescence has prolonged nowadays (Sawyer et al, 2018), it is important to include younger and older adolescents in the study of self- and group orientations. X. Wang et al (2023), for example, found in a cross-sectional study that compared with students in junior high schools, students in senior high schools were less likely to emphasize group well-being and social belongings and more likely to endorse life goals of personal happiness and independence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that adolescence has prolonged nowadays (Sawyer et al, 2018), it is important to include younger and older adolescents in the study of self- and group orientations. X. Wang et al (2023), for example, found in a cross-sectional study that compared with students in junior high schools, students in senior high schools were less likely to emphasize group well-being and social belongings and more likely to endorse life goals of personal happiness and independence.…”
Section: Discussionmentioning
confidence: 99%
“…X. Wang et al (2023), for example, found in a cross-sectional study that compared with students in junior high schools, students in senior high schools were less likely to emphasize group well-being and social belongings and more likely to endorse life goals of personal happiness and independence. The results suggest that the increase in self-orientation and the decrease in group orientation may continue in late adolescence.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%